TRADITIONAL ISLAM AND SACRED PRACTICES OF THE KAZAKH STEPPE IN THE HISTORICAL AND RELIGIOUS ANALYSIS OF THE FIGURE OF QARABURA (Journal of history, 2025)
The topic of traditional Islam in the Kazakh steppe represents an important aspect of the study of Islamic religiosity, as it is deeply connected to the nomadic way of life, the social structure, and the sacred geography of the region. In the context of a nomadic society, Islam became not only a religious doctrine but also an essential element in the formation of the cultural and social identity of the Kazakh people. One of the key features of traditional Islam was the veneration of saints, as well as the practice of pilgrimage (ziyarat), which allowed believers to strengthen their spiritual connection with Allah through visits to the mausoleums of holy figures (auliye). The veneration of saints, such as Qarabura, a friend and companion of Qoja Ahmed Yasawi, played a crucial role in reinforcing collective religiosity and preserving the cultural traditions of the Kazakh people. Sufi practices, particularly zikr (collective remembrance of Allah), played a central role in religious life, combining spiritual and social functions. Special attention was given to the role of the religious elite, including the kyz, who acted as keepers of knowledge and intermediaries between Islamic norms and local traditions, thereby facilitating the integration of Islam into the everyday life of the Kazakh people. The relevance of this research lies in the need to revise traditional approaches to the religious life of Kazakhs, as proposed by pre-revolutionary and Soviet historiography, which often distorted the understanding of Islamic religiosity. The study employs the theory of regional Islam, proposed by A. Abashin, as well as methods of historical and religious analysis, field research, including the search for informants and the collection of empirical data, and the study of the figure of Qarabura. This approach allows for a more accurate interpretation of the adaptation process of Islamic tradition in the context of a nomadic society. The hypothesis of the research is that traditional Islam in the Kazakh steppe represented a synthesis of orthodox religious teachings and Sufi spirituality, which was especially manifested in the figure of Qarabura and enabled Islam to harmoniously integrate into the cultural and social life of Kazakh society. The findings of the study highlight the importance of Islam in shaping and preserving the cultural identity of the Kazakh people.
Keywords: traditional Islam, sacred practices, Kazakh steppe, veneration of saints, Sufi orders, pilgrimage, regional Islam.